What is The Progression of Joint Deformity and Disability in Rheumatoid Arthritis Patients with Different Treatment Approaches? : A Systematic Review - Billy Jonathan; Veronica Winda Soesanto; Chaira Sultana Mazaya (International Medical Journal Corp. Ltd, 2025)
Introduction: Rheumatoid Arthritis (RA) is a chronic autoimmune disease leading to progressive joint destruction and disability. Modern management has shifted towards early, aggressive